2017
DOI: 10.20937/atm.2017.30.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and attributing the warming trend in sea and land surface temperatures

Abstract: RESUMENDebido a la variabilidad interna de baja frecuencia, las tendencias del calentamiento observadas y subyacentes en series de temperatura pueden ser marcadamente diferentes. Las temperaturas hemisféricas están caracterizadas por importantes discrepancias en las tendencias no lineales observadas, sugiriendo que los hemisferios norte y sur han respondido de manera diferente a los cambios en el forzamiento radiativo. Mediante la utilización de técnicas econométricas recientes es posible reconciliar estas dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…For the interhemispheric temperature asymmetry, natural variability partially masks the underlying anthropogenic global warming signal. This conclusion seems to be consistent with the evidence that Estrada et al (2017) have recently provided using a different statistical methodology. However, since AMO should be primarily controlled by external forcing, we want to study the relationship between AMO and ITA removing the forced signal in future research.…”
Section: Summary and Future Worksupporting
confidence: 92%
See 1 more Smart Citation
“…For the interhemispheric temperature asymmetry, natural variability partially masks the underlying anthropogenic global warming signal. This conclusion seems to be consistent with the evidence that Estrada et al (2017) have recently provided using a different statistical methodology. However, since AMO should be primarily controlled by external forcing, we want to study the relationship between AMO and ITA removing the forced signal in future research.…”
Section: Summary and Future Worksupporting
confidence: 92%
“…It is important to note that the analysis of the ITA time plot may suggest the existence of a structural break in the late 1960s. Estrada et al (2017), by applying the Perron-Yabu (PY) test to ITA, formally document the existence of a break in both the level and the slope of the trend -1967:12 and 1968:01-2016:12. The HQ criterion has selected p = 2 also in these sample periods.…”
Section: The Empirical Resultsmentioning
confidence: 99%
“…Although in some cases efforts are done to reduce the influence of external forcings (i.e., AMO is usually linearly detrended), part of this influence remains 35 . While separation of external forcing and natural variability in these indices is imperfect, it has been shown that they are useful in purging out low-frequency oscillations while retaining the trend produced by the response to changes in external forcing 3 , 27 , 28 , 37 , 39 . What is important is to get rid of the most of the low frequency movements associated with natural variability in order to get a more precise estimate of the break date.…”
Section: Methodsmentioning
confidence: 99%
“…Whether anthropogenic influences are factors driving climate/weather patterns in midlatitudes can be investigated by analyzing the spatial–temporal patterns of the response to increases in external forcings, the main common features of the regional temperature trends. Recent attribution studies showed that total and anthropogenic forcings are characterized by two marked changes in trend slope 3 , 4 , 27 , 28 , which are imparted to global and hemispheric temperatures, producing a temporal co-breaking pattern interpreted as a strong causality effect from anthropogenic forcing to temperatures 5 . The first is a marked increase in the rate of both forcings and warming near 1960, inducing the onset of the sustained global warming.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change has widely impacted human society and the natural environment, and an increasing number of studies have researched global warming [1]. According to the Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report (AR5), the average global surface temperature increased by approximately 0.85 • C from 1880 to 2010 [2].…”
Section: Introductionmentioning
confidence: 99%